Detection of Class 1 Integron among Klebsiella pneumoniae Clinical Isolates in Baghdad Hospitals - Jasim, Jasim S.; R. Hussein, Alyaa (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Extensively drug-resistant Klebsiella pneumoniae (K. pneumoniae) is a significant problem currently due to the increasing prevalence of this pathogen. Objectives: To underscore the growing threat of antibiotic-resistant K. pneumoniae by investigating the prevalence of class 1 integrons among selected multidrug-resistant (MDR) clinical isolates, with the goal of emphasizing the need for strengthened surveillance and targeted antimicrobial strategies. Methods: Seventy-four K. pneumoniae isolates have been identified out of 200 clinical samples from different clinical sources (urine, burns, blood, sputum, wounds). Isolates were obtained from November 2024 to March 2025, in Al-Kadhimiya Teaching Hospital and the Laboratory at College of Science Microbiology Department, University of Baghdad. The isolates were first detected by biochemical testing, chromogenic agar and later confirmed using the VITEK 2 method. Antimicrobial susceptibility was evaluated utilizing the disc diffusion technique (Kirby-Bauer method). The presence of the class 1 integron gene was confirmed via conventional PCR. Results: A total of 200 clinical samples were collected from the 74 K. pneumoniae isolates; 51 (68.9%) exhibited multidrug resistance. Resistance to cefotaxime was observed in 86%, followed by tetracycline (80%), while imipenem exhibited the highest sensitivity at 84%. Class 1 integron gene was identified in 80% of the 10 selected multidrug-resistant isolates. Conclusion: The high incidence of class 1 integrons in multidrug-resistant K. pneumoniae clinical isolates highlights the essential role of integrons in the spread of antibiotic resistance. This indicates the worldwide emergence of K. pneumoniae pathogenic strains resistant to colistin and carbapenems, highlighting the imperative for ongoing molecular surveillance and efficient antibiotic stewardship.